The defense function of the state: Traditional and modern understanding - Vračar Milinko S.; Barišić Igor I. (Srpska Politička Misao)
To understand a phenomenon means to grasp its essence, that is, all the characteristics that define it and distinguish it from other phenomena. Since the defense function of the state is a complex phenomenon encompassing biological, anthropological, philosophical, sociological, psychological, political, security, military, strategic, and other aspects, understanding its essence is no easy task. It requires a multidisciplinary approach and the application of concepts such as man, society, state, values, interests, power, politics, and strategy. The starting point in understanding its essence is undoubtedly the individual, given that instinctual needs for survival and security drive human nature. Since the origin and functioning of a political community are rooted in these human needs, the defense function of the state can be further clarified through an analogy with the same function in individuals. By applying this analogy, it can be concluded that defense belongs to the state's protective functions category. It differs from other functions of this type in that it is aimed at safeguarding the survival and vital values of the state from violent threats, and its protective action is also inherently violent. For this reason, until recently, the defense function of the state was equated with the military function. In recent decades, however, there has been a shift from the traditional militarycentric understanding of the state's defense function due to the growing significance of non-military threats to its survival and vital values. This has led to changes in the state's defense operations and, consequently, to a transformation in the essence of its defense function. While the object of the state's defense remains the same, its survival and vital values, the changes in the essence of its defense function emerge from the dialectical relationship between defense and attack. Therefore, the modern defense function of the state can be understood as a protective function by which the state, through the use of military and non-military instruments of national power in both peace and war, protects its survival and vital values from various military and non-military threats.